Spremembe izbranih demografskih in krajinskih kazalnikov v kraških krajinah notranje Slovenije v zadnjih štirih desetletjih - Ferreira, Andreja (Acta silvae et ligni, 2018)
We analysed basic demographic indicators (population size, population density) and selected landscape indicators (forest cover, number of forest patches, area of the largest forest patch, share of core areas in the forest) in the Karst landscapes of Inner Slovenia, their changes over four decades and the correlations between them. Using the Pearson correlation coefficient, we determined multiple statistically significant correlations between demographic and landscape indicators. In areas with higher population density, the share of forest has been significantly lower in both studied years. As expected, in areas with a higher share of forest, the share of core forest and the largest forest patches area are larger.
Keywords: demografski kazalniki; demographic indicators; forest; gozdovi; Karst; Karst landscapes of Inner Slovenia; krajina; krajinski kazalniki; Kras; Kraške krajine notranje Slovenije; landscape; landscape indicators; Slovenia; Slovenija